Efektivitas Pendekatan Rational Emotive Therapy Dalam Layanan Konseling Kelompok Untuk Mengatasi Gangguan Emosional Siswa - Siti Aisyah; Tohirin Tohirin (Fakultas Tarbiyah dan Keguruan, 2020)
This research aimed at knowing the effectiveness of Rational Emotive Therapy approach on group counseling service in overcoming student emotional disturbance. Quantitative pre-experimental research method was used in this research with pretest posttest one group design. The subjects of this research were the students experiencing high emotional disturbance, and the object was Rational Emotive Therapy approach on group counseling service in overcoming student emotional disturbance. Questionnaire, observation, and documentation were the techniques of collecting the data. Pearson product moment was used to test the questionnaire validity and Alpha Cronbach was for testing the reliability. The data were analyzed by using Wilcoxon test to know whether Rational Emotive Therapy approach on group counseling service in overcoming student emotional disturbance could be implemented. The research findings showed the mean score of student emotional disturbance before the treatment (pretest) was 112.9, and the mean score after the treatment (posttest) was 76.5. Based on the hypothesis test using Wilcoxon test, it was obtained that the probability score of Asymp. Sig. (2-tailed) 0.005 was lower than 0.05, it meant that Null hypothesis (H0) was rejected and Alternative hypothesis (Ha) was accepted. It could be concluded that Rational Emotive Therapy approach on group counseling service could be implemented to decrease student emotional disturbance.